Project-based entrepreneurial learning (PBEL): A blended model for startup creations at higher education institutions - R. Tri Priyono Budi Santoso; Sony Heru Priyanto; I. Wayan Ruspendi Junaedi; Donald Samuel Slamet Santoso; Lasmono Tri Sunaryanto (Journal of Innovation and Entrepreneurship, 2023)
This research aims to describe the dynamics of applying project-based entrepreneurial learning (PBEL) in creating startups at higher education institutions. Action research was used for eight participants as the research method by applying the PBEL model in the form of a narrative method. The results revealed that all university students can produce products, starting from prototypes until business products. The PBEL model drives successful startups. For the more effective startups, the PBEL model needs to add network marketing and funding to be applied. Future research is expected to address questions from the results of this study.
Keywords: 650; Startup; Entrepreneurial learning model; Narrative method; Project-based learning